Suitability assessment of neem formulations as biopesticide against honey bees and other pollinators - Pandey, Ashlsh (Journal of Ecophysiology and Occupational Health, 2017)
To study the effect of insecticidal spraying on non target insects have never been an important issue. In this article the foraging behaviour of honey bee worker and other pollinators was investigated after the spraying of insecticide. The study of antifeedancy and toxicity of two agricultural insecticides 0.07% endosulfan, 0.02% phosphamidon and three neem formulations 0.05% have been examined on three species of honey bees viz., Apis cerana indica F., Apis dorsata F., Apis mellifera L and other pollinators such as hymnopterous insect Vespa orentalis (Yellow jackets or hornets), lepidopterous insect Pieris brassicae (cabbage butterfly) and dipterous insect Hirmoneura bruanea (naenestrinid fly). Research results indicated that spray of these formulations of neem on mustard crop was found to be most effective @ 700 l/h. the effects were consistent and comparable to the endosulfan and phosphamidon. As a biological, plant derived prepration, neem formolatiom could be suitable for integrated pest management (IPM) programs, specially in small orchids, parks, tree growers in urban environments and on small private gardens. Such areas, toxic insecticides use should be avoided